Potret Dialog Islam dengan Budaya pada Masa Nabi SAW - Mohamad Shofin Sugito (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2014)
The Article describes and discusses about the relationship between Islam and culture in the Prophet's period.